The Effect of Inflammation on Bone - Epsley, Scott; Tadros, Samuel; Farid, Alexander; Kargilis, Daniel; Mehta, Sameer; Rajapakse, Chamith S. (Frontiers in Physiology, 2021)
Bone remodeling is the continual process to renew the adult skeleton through the sequential action of osteoblasts and osteoclasts. Nuclear factor RANK, an osteoclast receptor, and its ligand RANKL, expressed on the surface of osteoblasts, result in coordinated control of bone remodeling. Inflammation, a feature of illness and injury, plays a distinct role in skewing this process toward resorption. It does so via the interaction of inflammatory mediators and their related peptides with osteoblasts and osteoclasts, as well as other immune cells, to alter the expression of RANK and RANKL. Such chemical mediators include TNFα, glucocorticoids, histamine, bradykinin, PGE2, systemic RANKL from immune cells, and interleukins 1 and 6. Conditions, such as periodontal disease and alveolar bone erosion, aseptic prosthetic loosening, rheumatoid arthritis, and some sports related injuries are characterized by the result of this process. A thorough understanding of bone response to injury and disease, and ability to detect such biomarkers, as well as imaging to identify early structural and mechanical property changes in bone architecture, is important in improving management and outcomes of bone related pathology. While gut health and vitamin and mineral availability appear vitally important, nutraceuticals also have an impact on bone health. To date most pharmaceutical intervention targets inflammatory cytokines, although strategies to favorably alter inflammation induced bone pathology are currently limited. Further research is required in this field to advance early detection and treatments.